Legume Cover Crop Contributions to Ecological Nutrient Management in Upper Midwest Vegetable Systems - Perrone, Sharon; Grossman, Julie; Liebman, Alexander; Wells, Samantha; Sooksa-nguan, Thanwalee; Jordan, Nicholas (Frontiers in Sustainable Food Systems, 2022)
Cover cropping, especially with legumes (green manures) is a critical approach to ecological soil nutrient management as a means to meet Sustainable Development Goal (SDG) 2, addressing food security issues via sustainable agriculture approaches. However, cover cropping in some of the most intensified food production regions of the northern U.S. is challenged by short growing seasons and harsh winters with variable temperatures and increasingly erratic snowfall. In this study, we explore the potential of winter annual legume cover crops to augment soil organic carbon (C) and nitrogen (N) stocks within a horticultural cropping system under climate conditions that allow only modest cover crop biomass production. We compared hairy vetch, cereal rye, red clover, and a hairy vetch/rye biculture in a randomized complete block design at two Minnesota. Cover crops were established in fall and terminated in spring prior to sweet corn planting, and soils sampled both at pre-cover crop termination and two weeks post-termination. We determined several indicators of C/N dynamics, including microbial biomass C (MBC), permanganate-oxidizable C (POXC), particulate organic matter C and N (POMC and POMN, respectively), extractable soil N (EXTN), and potentially mineralizable N (PMN). Out of all species evaluated, vetch production increased soil EXTN the greatest, contributing two to 11 times more N to soils compared to non-vetch treatments. Overall, time of sampling, either pre-termination or post-, consistently impacted soil measurements, with p < 0.05 in 20 out of 24 soil parameter x environment combinations. In many of these cases, the NOCC control did not differ from some or all of the cover cropped treatments, suggesting disturbance effects may have been responsible for observed effects. Study results suggest that cover crops planted in colder northern climates during winter fallow periods can both supply nutrients following their spring termination, and contribute to longer term pools of nutrients that may supplement future nutrient additions. Overall findings contribute to our understanding of the role of cover crop legume systems in horticultural systems to meet SDG 2 outcomes.